ADULTS VERSUS ELDERS’ PERCEIVED UNDERSTANDING OF THE ENDANGERED LEXICONS OF THE NIGANG SASIH RITUAL IN MENYALI VILLAGE - Devi Trijayanti; I Gede Budasi; I Ketut Trika Adi Ana (Universitas Suryakancana, 2026)
The preservation of ritual lexicons is important in maintaining cultural identity, traditional knowledge, and intergenerational language transmission within Balinese society. However, modernization and the decreasing involvement of younger generations in traditional practices have gradually weakened the understanding of ritual language. This study investigated the perceived understanding of the endangered lexicons used in the Nigang Sasih ritual between adults and elders in Menyali Village, Buleleng Regency, Bali. The study aimed to describe the perceived understanding of adults and elders toward the ritual lexicons and to determine whether there was a significant difference between the two groups. This research employed a quantitative comparative cross-sectional design involving 100 respondents consisting of 50 adults and 50 elders selected through convenience and quota sampling techniques. Data were collected through a structured questionnaire containing 36 ritual lexicons previously documented by Lestari (2025). The collected data were analyzed using descriptive statistics and the Mann–Whitney U Test. The findings revealed a clear intergenerational difference in the perceived understanding of the endangered ritual lexicons. Adults generally demonstrated lower levels of perceived understanding, whereas elders showed higher levels of understanding toward the ritual lexicons. The statistical analysis also indicated a significant difference between the two groups, showing that elders possessed considerably stronger perceived understanding than adults. These findings suggest that the transmission of ritual lexicons within the community has become increasingly uneven across generations. Therefore, strengthening cultural transmission, community participation in rituals, and documentation efforts is essential to support the preservation of Balinese ritual language as part of intangible cultural heritage.